Preparation method, product and application of nano plate-shaped cobalt-based bimetallic phosphide heterostructure material
By loading cobalt-based bimetallic phosphides in situ on foam nickel iron, nanoplate-shaped cobalt-based bimetallic phosphide heterostructure materials are prepared, which solves the problem of slow reaction kinetics in electrolytic water hydrogen production technology, and achieves high activity and high stability electrode materials, which are suitable for large-scale production.
Patent Information
- Application Number
- CN202411581823.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
AI Technical Summary
In the existing electrolytic hydrogen production technology, the kinetics of semi-reaction hydrogen evolution and oxygen evolution are slow, resulting in relatively low energy conversion efficiency. Specific catalysts are needed to improve the reaction kinetics and thus improve the reaction efficiency.
Through the solvothermal method and high-temperature calcination method, a nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material was prepared by in situ loading cobalt-based bimetallic phosphide on foam nickel-iron foam, and used as electrodes to improve electrochemical performance.
This method effectively improves the activity and stability of the electrode, improves the electrochemical performance of hydrolysis hydrogen and oxygen analysis, and is low in cost, simple in operation, and is suitable for large-scale production.
Smart Images

Figure CN119615245A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material application for electrolyzing water, and in particular relates to a preparation method, product and application of a nano-plate-shaped cobalt-based bimetallic phosphide heterostructure material. Background Art
[0002] Hydrogen is a renewable clean energy source that will play an important role in the future. Its preparation, storage, transportation and application have attracted wide attention. At present, the main technical means of hydrogen production include hydrogen production from fossil energy reforming, hydrogen extraction from industrial by-products, and hydrogen production from water electrolysis. Traditional fossil fuel hydrogen production technology is relatively mature, but fossil fuel resources are limited. When burned, it will cause carbon emissions and seriously pollute the environment. Industrial by-product hydrogen refers to hydrogen extracted from by-products of industrial production such as coke oven gas and chlor-alkali tail gas. Due to process limitations, the purity of hydrogen produced by this method is low, and there are still pollution problems in the production process. Hydrogen production from water electrolysis is a green and efficient hydrogen production technology that uses electricity to decompose water molecules into hydrogen and oxygen. There are many technologies for hydrogen production from water electrolysis, such as alkaline water electrolysis, proton exchange membrane, high-temperature solid oxide and anion exchange membrane electrolysis. Hydrogen production from water electrolysis has high purity and can be used as an energy storage carrier to store surplus renewable energy. The entire process of hydrogen production from water electrolysis consumes only water and electricity, and does not consume other fossil resources. The process is simple, easy to operate, carbon-free, clean and pollution-free. The equipment occupies a small area, multiple equipment can be produced at the same time, and the operation is flexible. However, at the same time, water electrolysis is also an expensive hydrogen production technology. The main power consumption of hydrogen production is about 4.5~5.5kW hm -3 .
[0003] The problem with the half-reaction hydrogen evolution and oxygen evolution reactions is that their kinetics are slow, resulting in relatively low energy conversion efficiency, and specific catalysts are needed to improve the reaction kinetics and thus improve the reaction efficiency. Transition metals have good electrocatalytic HER and OER activity. They are cheap and abundant in reserves, and are ideal for replacing precious metal catalysts. Some transition metals and their alloys, oxides, sulfides, nitrides and phosphides have excellent activity and stability. For example, a Chinese patent with publication number CN108722452A discloses a functional metal phosphide catalyst, a preparation method thereof and its application. The method uses ZIF-67 as a raw material, adds nickel nitrate to etch and prepare nickel cobalt double hydroxide, and then uses hypophosphite as a phosphorus source, calcined at high temperature, and can prepare an oxygen-containing phase and a phosphide composite catalyst in situ, which has abundant active sites for water electrolysis and has better catalytic activity. And a Chinese patent with publication number CN106824238A discloses a bifunctional catalyst nano-sized Ni2P-CoP bimetallic phosphide for water electrolysis, which not only has excellent oxygen evolution activity in water electrolysis, but also shows excellent activity in hydrogen evolution test in water electrolysis.
[0004] The existing technology for preparing composite electrode materials of transition metal phosphides is mainly a coating method, and a binder needs to be added. Therefore, how to obtain composite electrode materials of transition metal phosphides by a simple preparation method is a current research hotspot. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a nano-plate-shaped cobalt-based bimetallic phosphide heterostructure material. The nano-plate-shaped cobalt-based bimetallic phosphide heterostructure material obtained by the simple preparation method can improve its electrochemical performance when applied to water electrolysis for hydrogen and oxygen evolution, and has high activity and high stability.
[0006] The present invention provides the following technical solutions:
[0007] A method for preparing a nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material, the preparation method comprising the following steps:
[0008] (1) dissolving nickel acetylacetonate, one of ferric acetylacetonate or molybdenum acetylacetonate, cobalt acetylacetonate and terephthalic acid, and reacting the dissolved nickel ferrous foam with the foam by a solvothermal method to obtain a cobalt-based bimetallic organic framework-loaded nickel ferrous foam;
[0009] (2) The nickel iron foam loaded with the cobalt-based bimetallic organic framework and sodium hypophosphite monohydrate are calcined at high temperature in a tubular furnace to obtain a nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material.
[0010] The present invention utilizes nickel-iron foam as a conductive substrate, in-situ grows a bimetallic organic framework by a hydrothermal method, and further prepares a nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material by further phosphating and calcining. The material can be used as an electrode and has excellent electrocatalytic water electrolysis and industrial application potential.
[0011] In step (1), the feeding amounts of nickel acetylacetonate, iron acetylacetonate or molybdenum acetylacetonate, cobalt acetylacetonate and terephthalic acid are 25-250 mg, 25-250 mg and 15-200 mg respectively; anhydrous ethanol, deionized water and N,N-dimethylformamide are used as solvents: the volume of anhydrous ethanol is 2-15 mL, the volume of deionized water is 2-15 mL, and the volume of N,N-dimethylformamide is 5-40 mL. The size of the nickel-iron foam is: 3 cm long×1 cm wide×1.0 mm thick.
[0012] In step (1), the solvent thermal reaction temperature is 80-200°C and the reaction time is 10-30h. At different temperatures and times, the properties of the solvent (density, viscosity, etc.) affect each other and vary greatly, and the dissolution, dispersion, reaction activity, etc. of the reactants are also different. The selected conditions can ensure the normal synthesis of the bimetallic phosphide material.
[0013] Preferably, the temperature of the solvothermal reaction is 120-150°C.
[0014] In step (2), the mass of nickel iron foam is 0.4-0.6 g, the mass of sodium hypophosphite monohydrate is 200-1000 mg, the calcination temperature is 250-450° C., and the reaction time is 2-6 h.
[0015] Preferably, the mass of sodium hypophosphite monohydrate is 500-1000 mg.
[0016] Preferably, the preparation method provided by the present invention is: 25-250 mg of nickel acetylacetonate, 25-250 mg of cobalt acetylacetonate and 15-200 mg of terephthalic acid are put into a volume of 2-15 mL of anhydrous ethanol, a volume of 2-15 mL of deionized water and a volume of 5-40 mL of N, N-dimethylformamide solution, ultrasonically dissolve the solid for 5-30 minutes, and add a foamed nickel-iron substrate (place the foamed nickel-iron (1*3) in concentrated hydrochloric acid and ultrasonicate for 30 minutes, clean the surface, and then ultrasonicate with deionized water and ethanol alternately for several times), then perform a solvent thermal reaction at 80-200°C for 10-30 hours, wait for the reaction to be complete and cool, take out the foamed nickel-iron, wash it with deionized water and anhydrous ethanol, and dry it. Finally, in a nitrogen atmosphere, the obtained nickel-iron foam is placed in a ceramic ark, which is placed downstream of the quartz tube, and 200-1000 mg of sodium hypophosphite monohydrate is placed downstream of the quartz tube, and is calcined at a high temperature of 250-450°C in a tubular furnace for 2-6 hours.
[0017] The present invention also provides a nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material obtained by the above preparation method.
[0018] The nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material is a nanoplate-shaped cobalt-nickel phosphide heterostructure material, a nanoplate-shaped cobalt-iron phosphide heterostructure material or a nanoplate-shaped cobalt-molybdenum phosphide heterostructure material.
[0019] Preferably, the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material is a nanoplate-shaped cobalt-nickel phosphide heterostructure material.
[0020] The loading amount of the cobalt-based bimetallic phosphide on the nickel-iron foam is 1-5 mg·cm -2 .
[0021] The heterogeneous structure material has a nanoplate-like morphology, and the nanoplate-like dimensions are 1 μm-4 μm in width, 1 μm-4 μm in length, and 0.1 μm-1 μm in thickness.
[0022] The present invention also provides an application of the above-mentioned nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material in the electrolysis of water to evolve hydrogen and oxygen.
[0023] Compared with the prior art, the present invention has the following technical effects:
[0024] (1) The present invention adopts a simple solvent thermal and high temperature calcination method to load the cobalt-based bimetallic phosphide in situ on the nickel-iron foam, which effectively improves the insufficient active sites and low activity of the nickel-iron foam, effectively improves the interface between the electrode and the electrolyte, and enhances the H + and OH - The transport kinetics of the electrodes are greatly improved, which greatly enhances the activity and stability of the electrodes.
[0025] (2) The preparation method of the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material provided by the present invention has low cost, simple operation, and is suitable for large-scale production.
[0026] (3) The nanoplate-like cobalt-based bimetallic phosphide heterostructure material prepared by the present invention is applied to water electrolysis and exhibits good electrochemical performance, and also provides a new idea as an electrocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD spectrum of nickel phosphide-cobalt phosphide material measured by D8 X-ray diffractometer of Bruker Corporation, USA, where: the abscissa X is the diffraction angle (2θ), and the ordinate Y is the relative diffraction intensity.
[0028] Figure 2 This is a surface morphology of the nickel phosphide-cobalt phosphide material prepared in Example 1 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).
[0029] Figure 3 This is the OER linear voltammetric test curve of the nickel phosphide-cobalt phosphide material prepared in Example 1 tested by Shanghai Chenhua Company's CHI 660E electrochemical workstation in 1M KOH.
[0030] Figure 4 This is the HER linear voltammetric test curve of the nickel phosphide-cobalt phosphide material prepared in Example 1 in 1M KOH tested by Shanghai Chenhua Company's CHI 660E electrochemical workstation.
[0031] Figure 5 This is the OWS linear voltammetric test curve of the nickel phosphide-cobalt phosphide material prepared in Example 1 in 1M KOH tested by Shanghai Chenhua Company's CHI 660E electrochemical workstation.
[0032] Figure 6 It is the electrochemical specific surface area of the nickel phosphide-cobalt phosphide material prepared in Example 1 in 1M KOH tested by Shanghai Chenhua Company's CHI 660E electrochemical workstation for HER.
[0033] Figure 7 The stability test of the HER in 1M KOH of the nickel phosphide-cobalt phosphide material prepared in Example 1 was conducted by Shanghai Chenhua Company's CHI 660E electrochemical workstation.
[0034] Figure 8 This is a surface morphology of the nickel phosphide material prepared in Comparative Example 2 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).
[0035] Fig. 9 This is the OER linear voltammetric test curve of the nickel phosphide material prepared in Comparative Example 2 tested by Shanghai Chenhua Company's CHI 660E electrochemical workstation in 1M KOH.
[0036] Fig.10 This is a surface morphology of the cobalt phosphide material prepared in Comparative Example 3 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).
[0037] Fig.11 This is the OER linear voltammetric test curve of the cobalt phosphide material prepared in Comparative Example 3 tested by Shanghai Chenhua Company's CHI 660E electrochemical workstation in 1M KOH.
[0038] Fig.12 It is the LSV curve of HER of different cobalt-based bimetallic phosphides prepared in Examples 2 and 3 in 1 M KOH tested by Shanghai Chenhua Company CHI 660E electrochemical workstation.
[0039] Fig.13 It is the LSV curve of HER of Ni2P / CoP electrocatalyst prepared in Examples 4 and 5 in 1M KOH at different hydrothermal temperatures tested by Shanghai Chenhua Company's CHI 660E electrochemical workstation.
[0040] Fig.14 It is the LSV curve of HER of different electrocatalysts in 1M KOH at different masses of sodium hypophosphite monohydrate prepared in Example 6 and Comparative Example 1 tested by Shanghai Chenhua Company CHI 660E electrochemical workstation.
[0041] Fig.15 This is a surface morphology of the cobalt iron phosphide material prepared in Example 2 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).
[0042] Fig.16 This is a surface morphology of the cobalt molybdenum phosphide material prepared in Example 3 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).
[0043] Fig.17 This is a surface morphology of the phosphide material prepared in Example 4 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).
[0044] Fig.18 This is a surface morphology of the phosphide material prepared in Example 5 observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM). DETAILED DESCRIPTION
[0045] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0046] Example 1
[0047] Weigh 200 mg of nickel acetylacetonate, 200 mg of cobalt acetylacetonate and 250 mg of terephthalic acid and put them into 2 mL of anhydrous ethanol, 2 mL of deionized water and 30 mL of N, N-dimethylformamide solution, ultrasonicate for 5-30 minutes to dissolve the solid, add a piece of nickel-iron foam substrate, and then perform solvent thermal reaction at 150°C for 12 hours. After the reaction is complete and cooled, take out the nickel-iron foam, wash it with deionized water and anhydrous ethanol, and dry it. Finally, in a nitrogen atmosphere, place the obtained nickel-iron foam in a ceramic ark, place it downstream of the quartz tube, place 500 mg of sodium hypophosphite monohydrate upstream of the quartz tube, and calcine it at high temperature in a tubular furnace at 350°C for 3 hours to obtain a nickel phosphide-cobalt phosphide material (nanoplate-shaped cobalt-nickel phosphide heterostructure material).
[0048] Figure 1 As shown, according to XRD, the synthesized sample corresponds to the physical phase of nickel phosphide-cobalt phosphide material, indicating that the synthesis is successful.
[0049] Step 2: Characterization of the surface morphology of nickel phosphide-cobalt phosphide materials and their water electrolysis performance.
[0050] The nickel phosphide-cobalt phosphide material prepared in Example 1 was subjected to SEM testing, and the results obtained are as follows: Figure 2 As shown, the loading amount is 0.3 mg cm -2 .
[0051] The electrochemical performance of nickel-iron foam was tested in the potential ranges of 0.2-1.3 V vs. RHE, -1.5-1.5 V vs. RHE and 1-2 V vs. RHE, respectively. Figure 3 , Figure 4 and Figure 5 Specifically, at 500 mA cm-2 At a current density of , the overpotential of HER is 261 mV, the overpotential of OER is 342 mV, and the voltage of complete water splitting is 1.85 V.
[0052] Figure 6 In a three-electrode system, cyclic voltammetry tests were performed in the non-Faraday range, indicating that it has a high electrochemically active specific surface area.
[0053] Figure 7 The stability test was carried out in the range of 0.05-0.30V vs.RHE, indicating that it has high stability.
[0054] Example 2-3
[0055] The specific experimental steps and experimental parameters in Example 2 and Example 3 are the same as those in Example 1, except that in step (1), ferric acetylacetonate and molybdenum acetylacetonate are weighed instead of nickel acetylacetonate. The amount of ferric acetylacetonate in Example 2 is 200 mg; the amount of molybdenum acetylacetonate in Example 3 is 200 mg. Fig.12 As shown in Figure 2, the overpotentials of HER for different cobalt-based bimetallic phosphides are 261 mV, 327 mV, and 328 mV, respectively, at 500 mA cm -2 At a current density of Fig.15 As shown in FIG. , it is a nanoplate-shaped cobalt iron phosphide with a width of 3 μm, a length of about 3 μm, and a thickness of 0.5 μm. Fig.16 As shown, nanoplate-shaped cobalt molybdenum phosphide has a width of 2.1 μm, a length of about 2.8 μm, and a thickness of 1 μm.
[0056] Embodiment 4-5
[0057] The specific experimental steps and experimental parameters in Examples 4 and 5 are the same as those in Example 1, except that the hydrothermal temperature in step (1) is different. The hydrothermal temperature in Example 4 is 120°C; the hydrothermal temperature in Example 5 is 140°C. Fig.13 As shown in Figure 2, the HER overpotentials at 150°C, 140°C, and 120°C are 261 mV, 293 mV, and 280 mV, respectively. -2 At a current density of Figure 17-18 As shown, at a temperature of 140°C, the electrocatalyst material has a length of 2.2 μm and a thickness of 0.2 μm. At a temperature of 120°C, the electrocatalyst material has a length of 2.4 μm and a thickness of 0.1 μm.
[0058] Example 6
[0059] The specific experimental steps and experimental parameters in Example 6 are the same as those in Example 1, except that the amount of sodium hypophosphite monohydrate used in step (2) is different. The mass of sodium hypophosphite monohydrate in Example 6 is 1 g. The dimensions of the electrocatalyst material prepared in this example are respectively about 1 μm in length and 0.2 μm in thickness.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the mass of sodium hypophosphite monohydrate is 0 g.
[0062] like Fig.14 As shown, for Example 1, Example 6 and Comparative Example 1, under different masses of sodium hypophosphite monohydrate, at 500 mA cm -2 At current densities of , the HER overpotentials are 261mV, 268mV, and 410mV, respectively.
[0063] Comparative Example 2
[0064] Step 1, preparation and characterization of nickel phosphide materials
[0065] Referring to Example 1, a nickel phosphide-based material was synthesized.
[0066] Step 2, preparation and characterization of nickel phosphide materials
[0067] Take 200 mg of nickel acetylacetonate and 200 mg of terephthalic acid and put them into 2 mL of anhydrous ethanol, 2 mL of deionized water and 30 mL of N,N-dimethylformamide solution, ultrasonicate for 5-30 minutes to dissolve the solid, add a piece of nickel-iron foam substrate, and then carry out solvent thermal reaction at 150°C for 12 hours. After the reaction is complete and cooled, take out the nickel-iron foam, wash it with deionized water and anhydrous ethanol, and dry it. Finally, in a nitrogen atmosphere, place the obtained nickel-iron foam in a ceramic ark, place it downstream of the quartz tube, and place 500 mg of sodium hypophosphite monohydrate upstream of the quartz tube. It is calcined at a high temperature of 350°C in a tubular furnace for 3 hours to obtain a nickel phosphide material. Figure 8 , it can be observed that its morphology is an ultra-thin nanosheet material.
[0068] Step 3, assemble the three-electrode system, the OER performance is as follows Fig. 9 shown.
[0069] Comparative Example 3
[0070] Step 1, preparation and characterization of cobalt phosphide materials
[0071] Referring to Example 1, a cobalt phosphide material was synthesized.
[0072] Step 2, preparation and characterization of cobalt phosphide materials
[0073] Weigh 200 mg of cobalt acetylacetonate and 200 mg of terephthalic acid and put them into 2 mL of anhydrous ethanol, 2 mL of deionized water and 30 mL of N,N-dimethylformamide solution. Ultrasonicate for 5-30 minutes to dissolve the solid, add a piece of nickel-iron foam substrate, and then carry out solvent thermal reaction at 150°C for 12 hours. After the reaction is complete and cooled, take out the nickel-iron foam, wash it with deionized water and anhydrous ethanol, and dry it. Finally, in a nitrogen atmosphere, place the obtained nickel-iron foam in a ceramic ark and place it on the upstream of the quartz tube. Place 500 mg of sodium hypophosphite monohydrate on the upstream of the quartz tube and calcine it in a tubular furnace at 350°C for 3 hours to obtain a cobalt phosphide material. Fig.10 The surface morphology of the catalyst is nanosheet-like.
[0074] Step 3, assemble the three-electrode system, the OER performance is as follows Fig.11 shown.
[0075] Comparing the OER performance of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that at 500 mA cm -2 At a current density of , the OER overpotential of Ni2P is 352 mV, and the overpotential of CoP is 403 mV.
Claims
1. A method for preparing a nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material, characterized in that: The preparation method comprises the following steps: (1) dissolving nickel acetylacetonate, one of ferric acetylacetonate or molybdenum acetylacetonate, cobalt acetylacetonate and terephthalic acid, and reacting the dissolved nickel ferrous foam with the foam by a solvothermal method to obtain a cobalt-based bimetallic organic framework-loaded nickel ferrous foam; (2) The nickel iron foam loaded with the cobalt-based bimetallic organic framework and sodium hypophosphite monohydrate are calcined at high temperature in a tubular furnace to obtain a nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material.
2. The method for preparing the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 1, characterized in that: In step (1), the feeding amounts of nickel acetylacetonate, iron acetylacetonate or molybdenum acetylacetonate, cobalt acetylacetonate and terephthalic acid are 25-250 mg, 25-250 mg and 15-200 mg, respectively.
3. The method for preparing the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 1, characterized in that: In step (1), the temperature of the solvothermal reaction is 80-200° C., and the time of the solvothermal reaction is 10-30 hours.
4. The method for preparing the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 120-150°C.
5. The method for preparing the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 2, characterized in that: In step (2), the mass of the nickel iron foam loaded with the cobalt-based bimetallic organic framework is 0.4-0.6 g, the mass of the sodium hypophosphite monohydrate is 200-1000 mg, the calcination temperature is 250-450° C., and the reaction time is 2-6 h.
6. The method for preparing the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 1, characterized in that: The mass of sodium hypophosphite monohydrate is 500-1000 mg.
7. A nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material obtained according to the preparation method according to any one of claims 1 to 6.
8. The nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 7, characterized in that: The loading amount of the cobalt-based bimetallic phosphide on the nickel-iron foam is 1-5 mg·cm -2 .
9. The nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 7, characterized in that: The heterogeneous structure material has a nanoplate-like morphology, and the nanoplate-like dimensions are 1 μm-4 μm in width, 1 μm-4 μm in length, and 0.1 μm-1 μm in thickness.
10. Use of the nanoplate-shaped cobalt-based bimetallic phosphide heterostructure material according to claim 7 in the electrolysis of water for hydrogen and oxygen evolution.
Citation Information
Patent Citations
Bifunctional catalyst nanoscale Ni2P-CoP bimetal phosphide for electrolyzing water
CN106824238A
Dual-function metal phosphide catalyst as well as preparation method and application thereof
CN108722452A